INSTITUTIONALIZATION OF THE PARTY SYSTEM IN KAZAKHSTAN AND RUSSIA: COMPARATIVE ANALYSIS Part II - KARMAZINA, Lydia (CENTRAL ASIA AND THE CAUCASUS, 2009)
A government that has closed its ranks to form a party (the academic community has aptly tagged this “the party of power”) is another striking feature of the period under review. The party of power competes with all the other parties for the electorate’s votes.1 This political phenome none of Russia and Kazakhstan is a logical product of authoritarian democracy realized through the super-presidential form of government in both countries. Since 1990 the Russian establishment has made several attempts to set up a party of power—the Democratic Russia Movement (1990); the Party of Russian Unity and Harmony—PRES (1993); the Russia’s Democratic Choice Party (1994); Russia is Our Home (1995)2 —each of these structures being genetically tied to its predecessor which served its basis. The Russia is Our Home Party was based on the pro-governmental movements Russia’s Democratic Choice and PRES.3 Success came in December 2001 in the form of the all-Russia political party “Unity and Fatherland—United Russia,” which in 2005 acquired a new name—the All-Russia Political Party United Russia (UR) rooted in the election blocs “Unity” and “Fatherland—All Russia” which were set up for the 1999 Duma elections to support the course being steered by Acting President Vladimir Putin. It was thanks to the nationwide popularity of President Putin, who, in turn, supported the new party at the 2003 and 2007 elections and to the much stronger position of the government in Russia (the elites consolidated around the president, who built up the vertical of power)4 that United Russia won the constitutional majority in the State Duma during both elections to become the strongest political party in the Russian Federation’s history. It left two other old-timers of the RF Federal Assembly (the Communist Party of the RF and the Liberal-Democratic Party) far behind.